Human and Nature Minding Automation An Overview of Concepts, Methods, Tools and Applications - Tzafestas, Spyros G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book presents an overview of the fundamental principles, problems and issues of the modern field of "human and nature-minding automation and industrial systems". The ultimate goal of "symbiosis" of automation and technology between humans and nature is to assure global technological, environmental and economic sustainability. Human-minding automation is possible by employing concepts and techniques from the human factors field, including job satisfaction, human-friendly interfaces and human values. Nature-minding industrial activity and human development can be achieved by considering as a whole the human, economic, natural and cultural resources in the short and long term. In particular, nature-minding design selects the production methods and technologies that have minimum impact to the environment. The book provides a comprehensive tutorial introduction in all these problems and solution methodologies. It is suitable for students, scientists and professionals interested in the human and environmental issues of the use of technology and automation in modern society. The depth of presentation is kept at a level sufficient for the reader to get a clear picture of the problems and their solutions. The book gives more than 700 references and related web sites.
Keywords: Engineering; Computer science; Life sciences; Environmental pollution; Engineering; Robotics and Automation; User Interfaces and Human Computer Interaction; Popular Science in Nature and Environment; Industrial Pollution Prevention; Computers and Society